An Analysis of Peer Ratings as Predictors and Criterion Measures and a Proposed New Application - Nisi, Angelo S. De; Mitchell, Jimmy L. (Academy of Management Review, 1978)
Angelo S. de Nisi, Jimmy L. Mitchell, An Analysis of Peer Ratings as Predictors and Criterion Measures and a Proposed New Application, The Academy of Management Review, Vol. 3, No. 2 (Apr., 1978), pp. 369-374